Increased Levels of Granulocytic Myeloid-Derived Suppressor Cells in Peripheral Blood and Tumour Tissue of Pancreatic Cancer Patients - Yazan S. Khaled; Basil J. Ammori; Eyad Elkord (Journal of Immunology Research)
Pancreatic cancer (PC) often presents late with poor survival. While role of immunosuppressive cells in preclinical studies provided help to develop immunotherapeutic agents, these cells remain under investigation in PC. The aim of this study was to characterise the different subsets of myeloid-derived suppressor cells (MDSCs) and evaluate their level and function in the circulation and tissue of PC patients. Significant increases in circulating and tumour-infiltrating granulocytic (Lin-HLA-DR-CD33+CD11b+CD15+), but not monocytic (Lin-HLA-DR-CD14+), MDSCs were detected in PC patients when compared with healthy donors and patients with chronic pancreatitis. The circulating MDSCs from PC patients expressed arginase 1, which represents their functional state. Blood levels of MDSCs showed no association with PC stage or preoperative levels of tumour markers. These findings provide a first characterisation of the phenotype of different subsets of peripheral and local MDSCs in PC patients and suggest that the frequency and contribution of these cells are predominantly granulocytic. This information demonstrates that MDSCs play a role in pancreatic cancer and future large validation studies may help in the development of new immunotherapeutic strategies to inhibit or eliminate MDSC function.